COST-BENEFIT ANALYSIS OF LEACHATE TREATMENT SYSTEM AT BANTARGEBANG INTEGRATED WASTE MANAGEMENT FACILITY - Leony, Vanecia
TPST Bantargebang is an integrated waste management facility located in Kota Bekasi. In the landfilling process, there is a potential for environmental pollution due to leachate. To overcome this, TPST Bantargebang owns three Instalasi Pengolahan Lindi (IPL). The percentage of leachate handling for the overall IPL is quite low due to the limited IPL handling capacity. Untreated leachate runoff can cause river pollution. With the existing conditions, Business as Usual scenario can be determined from the leachate treatment system at TPST Bantargebang. The prediction of leachate generation is calculated to determine the quantity of leachate that should be processed. The leachate handling capacity of each IPL is determined from the result of discharge calculation based on the processing organic load. The alternatives leachate treatment systems are based on the leachate handling capacity of each scenario. Utilization of IPL 2 for scenario 1, IPL 2 and IPL 3 for scenario 2, as well as IPL 1, IPL2, and IPL 3 for scenario 3. Cost and benefit analysis is applied to each alternative. The economic feasibility of each alternative is determined by calculating the value of the benefit-cost ratio (BCR) and net present value (NPV).